Peran Kebijakan Dividen dalam Tata Kelola Perusahaan yang Dikontrol oleh Keluarga - Tania, Ivon Natasia; Roida, Herlina Yoka; Martono, Cyrillius (Jurnal Samudra Ekonomi dan Bisnis, 2024)
The research aims to examine how family company governance influences dividend policy in the context of minority shareholder protection in 345 observations of family companies listed on the Indonesia Stock Exchange (BEI) during the 2016-2020 period. The results of this research using panel regression (random effects model) show that family ownership concentration has a non-linear relationship to dividend policy, while the level of family involvement through the board of directors and board of commissioners has a statistically negative effect on dividend policy. However, the existence of independent commissioners and lender supervision do not have a significant effect on dividend policy. Overall, this research supports agency theory that family involvement in the company can give rise to agency conflicts with minority shareholders through dividend distribution.